القانون في عالم الاقتصاد: أهميته ودو ره في ضبط السوق والنشاط الاقتصادي: Law in the world of economics: its importance and role in controlling the market and economic activity - جلطي غالم (Journal of North African Economies, 2025)
The preparation of a legal system that controls and activates economic practices in all its dimensions and that protects economic operators from the abuses of the authority or attempts to deviate from its natural course, such as the protection of property rights, respect for contracts, charters, competition laws, the formation of prices according to market mechanisms (supply and demand) and the protection of the producer and the consumer, was and still represents the cornerstone. The functioning and effectiveness of markets in the light of the market economy, which is considered a priority by the state as a market regulator after its withdrawal from economic activity. Accordingly, we try, through this research paper, to shed light on the importance and role of law in controlling the market and economic activity, and to highlight the trend towards institutional thought for the effectiveness of markets.